Adhesive composition containing chloroprene polymer latex

By adding a tackifier and a chloroprene polymer latex to the chloroprene polymer latex to form an adhesive composition, the chloroprene polymer latex adhesive on the polyolefin resin in the prior art is solved. The problem of insufficient adhesiveness and heat resistance achieves high adhesion and heat creep resistance, which is suitable for high temperature environments of automotive interior materials.

CN119213092APending Publication Date: 2024-12-27RESONAC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041408.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-08
Filing Date
2023-07-07
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing chloroprene polymer latex adhesives have poor storage stability, complex processes, and the need for plasticizers and crosslinkers in improving the adhesion and heat resistance to polyolefin resins, which are difficult to meet the needs of automobiles. High temperature use requirements for decorative materials.

Method used

By using a method that does not require plasticizers or crosslinkers, a specific content of tackifier and chlorinated polyolefin resin are added to the chloroprene polymer latex, the adhesive composition is formed to enhance adhesion and resistance. Thermal creep.

Benefits of technology

It achieves high adhesion and heat resistance to non-polar materials, especially without creep under high temperature conditions, and is suitable for adhesives for automotive interior materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005141266350000141
    Figure BDA0005141266350000141
  • Figure BDA0005141266350000151
    Figure BDA0005141266350000151
  • Figure BDA0005141266350000161
    Figure BDA0005141266350000161
Patent Text Reader

Abstract

The present invention addresses the problem of developing a chloroprene polymer latex adhesive composition that has excellent storage stability and that has both excellent adhesiveness with non-polar materials such as olefins and excellent thermal creep resistance, without requiring a complicated step, for use as an automotive interior material. [Solution] An adhesive composition containing a chloroprene polymer latex, characterized by containing a chloroprene polymer latex (A), a tackifier (B), and a chlorinated polyolefin resin (C), the content of a gel component of a chloroprene polymer in the chloroprene polymer latex (A) being more than 0% by mass but 50% by mass or less, and the content of a gel component of a chloroprene polymer in the chloroprene polymer latex (A) being less than 0% by mass and less than 50% by mass. The softening point of the tackifier (B) is 85 DEG C or more, the softening point of the chlorinated polyolefin resin (C) is less than 80 DEG C, the tackifier (B) is more than 5 parts by mass but less than 30 parts by mass per 100 parts by mass of the solid content of the chloroprene polymer latex (A), and the tackifier (B) is more than 5 parts by mass but less than 30 parts by mass per 100 parts by mass of the solid content of the chloroprene polymer latex (A). The amount of the chlorinated polyolefin resin (C) is 6 parts by mass or more but less than 30 parts by mass, and the adhesive composition containing the chloroprene polymer latex does not contain a cross-linking agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a latex adhesive composition, an adhesive layer and a laminate using a chloroprene polymer latex. Background Art

[0002] Chloroprene polymer is a polychloroprene obtained by emulsion polymerization of 2-chloro-1,3-butadiene, and has high cohesive force and crystallinity. Chloroprene polymer is mainly produced by emulsion polymerization, and chloroprene polymer latex in which polymer particles are dispersed in water after polymerization can be applied to a substrate without dissolving the chloroprene polymer in a solvent, and is used as an environmentally friendly water-based adhesive in furniture, shoes, civil engineering, diving suits, etc.

[0003] In recent years, as the regulation of volatile organic compounds has been strengthened worldwide, a shift has been made from solvent-based adhesives to water-based adhesives with less environmental impact, and the demand for water-based adhesives of chloroprene polymer latex has increased. However, polyolefin resins used as automotive interior materials such as seats and instrument panels are non-polar materials, so the polarity difference with chloroprene polymers is large, and it is extremely difficult to show sufficient bonding strength to polyolefin resins. Examples of polyolefin resins include polyethylene resins and polypropylene resins.

[0004] Polyolefin resins are inexpensive and lightweight, and are used in a wide range of fields, including automotive interiors and building interiors, to improve fuel efficiency. If polyolefin resins cannot be bonded, the manufacturing process of the product is limited, so the problem is solved by modifying the bonding surface through oxidation treatment or chemical treatment, using appropriate primers and crosslinking agents, etc.

[0005] In recent years, water-based adhesives that do not require the above-mentioned surface treatment are required from the perspective of reducing the cost of surface treatment. Furthermore, in automotive interior materials, when the temperature inside the car rises to a high temperature (e.g., 80°C) in summer, creep such as floating and peeling occurs if the heat resistance of the adhesive is insufficient. In the field requiring such heat-resistant creep, water-based adhesives that fully meet the required characteristics have not been developed. Therefore, in order to meet these needs, research has been conducted on improving the adhesion of chloroprene polymer latex adhesives to polyolefin resins.

[0006] Patent Document 1 discloses a polychloroprene polymer latex adhesive composition, which is characterized by containing a carboxyl-modified chloroprene polymer latex (a), a chlorinated polyolefin resin emulsion (b), and zinc oxide (c), wherein the carboxyl-modified chloroprene polymer latex (a) contains a copolymer of a chloroprene monomer and an ethylenically unsaturated carboxylic acid, and polyvinyl alcohol as a nonionic surfactant.

[0007] Patent Document 2 discloses a chloroprene rubber latex adhesive composition comprising a chloroprene rubber latex (a) synthesized using a rosin acid salt-based activator, a chloroprene rubber latex (b) having a carboxyl group or a hydroxyl group in the molecule, and a carbodiimide compound.

[0008] Patent document 3 discloses a chloroprene-based latex-type adhesive composition, characterized in that, relative to 100 parts by weight of the solid content of a chloroprene polymer latex (A) having a gel content of less than 40%, the amount (solid content) of a tackifier resin emulsion (B) is 1 to 100 parts by weight, the amount (solid content) of a chlorinated polyolefin resin emulsion (C) is 1 to 20 parts by weight, and the amount of a titanium chelate (D) is 0.1 to 10 parts by weight.

[0009] Patent Document 4 discloses a chloroprene rubber latex adhesive composition comprising a carboxyl-modified chloroprene copolymer latex (A), a chloroprene polymer latex (B), and a chlorinated polyolefin resin emulsion (C), wherein the carboxyl-modified chloroprene copolymer latex (A) comprises a copolymer of a chloroprene monomer and an ethylenically unsaturated carboxylic acid, and polyvinyl alcohol, and the chloroprene polymer latex (B) comprises a chloroprene homopolymer or a copolymer of a chloroprene monomer and other monomers, and a rosin acid metal salt, and the content ratio of the carboxyl-modified chloroprene copolymer latex (A) to the chloroprene polymer latex (B) is 80:20 to 20:80 in terms of solid content conversion ratio.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 2017-222804

[0013] Patent Document 2: Japanese Patent Application Publication No. 2011-63672

[0014] Patent Document 3: Japanese Patent Application Publication No. 2002-275442

[0015] Patent Document 4: International Publication No. 2018 / 043586 Summary of the invention

[0016] Problems to be solved by the invention

[0017] In Patent Document 1, a chloroprene copolymer latex obtained by copolymerizing an ethylenically unsaturated carboxylic acid is used to improve the adhesive performance of the chloroprene polymer latex adhesive to a polyolefin resin. However, a complicated operation such as copolymerizing the ethylenically unsaturated carboxylic acid is necessary.

[0018] Patent Document 2 discloses that two chloroprene polymer latexes having a specific gel component content are blended and a carbodiimide compound is further added as a crosslinking agent to improve adhesion and heat resistance. However, the addition of the crosslinking agent results in poor storage stability.

[0019] Patent Document 3 discloses that olefin adhesion resistance and thermal creep resistance are improved by blending a titanium chelate as a crosslinking agent into a chloroprene polymer latex having a specific gel component content or less. However, the crosslinking agent has problems such as poor storage stability and complicated mixing work.

[0020] In Patent Document 4, although the bonding strength and heat creep resistance are improved by blending a carboxyl-modified chloroprene copolymer latex and a chloroprene polymer latex at a specific blending ratio, there are problems that the process itself and the mixing operation are complicated because the carboxyl-modified chloroprene copolymer latex is produced by copolymerization and the chloroprene polymer latex needs to be blended.

[0021] Therefore, the present invention aims to develop a chloroprene polymer latex adhesive composition for automobile interior materials that has excellent adhesion to non-polar materials such as olefins and heat creep resistance and good storage stability without going through complicated steps such as mixing, blending and copolymerization of plasticizers.

[0022] Means for solving problems

[0023] The present inventors have conducted various studies to solve the above problems and have found that the above problems can be solved by adding a tackifier (B) and a chlorinated polyolefin resin (C) to a chloroprene polymer latex (A) having a specific gel component content.

[0024] That is, the present invention relates to a chloroprene polymer latex-containing adhesive composition and an adhesive layer comprising the following chloroprene polymer latex (A), a tackifier (B) and a chlorinated polyolefin resin (C).

[0025] That is, the present invention has the following configurations.

[0026] [1] An adhesive composition containing a chloroprene polymer latex, characterized in that it contains a chloroprene polymer latex (A), a tackifier (B) and a chlorinated polyolefin resin (C), wherein the content of the gel component of the chloroprene polymer in the chloroprene polymer latex (A) is more than 0% by mass and less than 50% by mass, at least one of the tackifiers (B) has a softening point of 85° C. or higher, and the chlorinated polyolefin resin (C) has a softening point of less than 80° C.

[0027] The amount of the tackifier (B) is more than 5 parts by mass and less than 30 parts by mass relative to 100 parts by mass of the solid content of the chloroprene polymer latex (A),

[0028] The chlorinated polyolefin resin (C) is 6 parts by mass or more and less than 30 parts by mass based on 100 parts by mass of the solid content of the chloroprene polymer latex (A).

[0029] The adhesive composition containing the chloroprene polymer latex does not contain a crosslinking agent.

[0030] [2] The adhesive composition containing a chloroprene polymer latex according to [1], wherein the chloroprene polymer is a chloroprene homopolymer or a copolymer containing at least chloroprene and 2,3-dichloro-1,3-butadiene.

[0031] [3] The adhesive composition containing chloroprene polymer latex according to [1] or [2], wherein the tackifier (B) comprises at least one of a rosin resin, a rosin ester resin, a terpene phenol resin, and an alicyclic petroleum resin.

[0032] [4] The adhesive composition containing chloroprene polymer latex according to [1] to [3], wherein the tackifier (B) has a softening point of 85°C or higher and 250°C or lower.

[0033] [5] The adhesive composition containing chloroprene polymer latex according to [1] to [4], further comprising a metal oxide or hydroxide.

[0034] [6] The adhesive composition containing chloroprene polymer latex according to [1] to [5], further comprising a thickener.

[0035] [7] An adhesive layer comprising the adhesive composition containing chloroprene polymer latex according to [1] to [6].

[0036] [8] A laminated body comprising two adherends laminated together via the adhesive composition containing a chloroprene polymer latex according to any one of [1] to [6].

[0037] [9] The laminate according to [8], wherein at least one of the adherends is a foamed organic material.

[0038]

[10] The laminate according to [9], wherein the foamed organic material of the laminate is any one of polypropylene, polyethylene, and polyurethane.

[0039] Effects of the Invention

[0040] The adhesive composition containing the chloroprene polymer latex of the present invention has high adhesive strength and excellent heat creep resistance, and is particularly excellent in adhesion to non-polar materials.

[0041] Therefore, the chloroprene polymer latex adhesive composition of the present invention is suitable as an adhesive for adherends made of polyolefin resins, polyurethanes, etc. Furthermore, the chloroprene polymer latex of the present invention does not creep even when exposed to high temperatures (e.g., 80° C.) such as adhesives for automobile interior materials, and can be used suitably. DETAILED DESCRIPTION

[0042] Hereinafter, embodiments of the present invention will be described in detail.

[0043] The chloroprene polymer latex-containing adhesive composition [1] of the present embodiment contains a chloroprene polymer latex (A), a tackifier (B), and a chlorinated polyolefin resin (C).

[0044] <Chloroprene polymer latex (A)>

[0045] The chloroprene polymer latex (A) is a material in which chloroprene polymer particles are dispersed in water.

[0046] The chloroprene polymer in the chloroprene polymer latex (A) is a homopolymer of 2-chloro-1,3-butadiene (hereinafter also referred to as “chloroprene”) or a copolymer containing at least chloroprene as a monomer component.

[0047] Chloroprene polymer

[0048] The chloroprene polymer constituting the chloroprene polymer latex (A) of the present embodiment is a homopolymer of chloroprene or a copolymer of chloroprene. It should be noted that, in the case of a copolymer, it can be any one of a copolymer of chloroprene and 2,3-dichloro-1,3-butadiene, a copolymer of chloroprene and a monomer capable of copolymerization other than this, and a copolymer of chloroprene and 2,3-dichloro-1,3-butadiene and a monomer capable of copolymerization other than this. In addition, two or more units derived from monomers capable of copolymerization other than this can be copolymerized as needed. The chloroprene polymer is preferably a polymer containing more than 50 mol% of chloroprene as a monomer component.

[0049] The chloroprene polymer is preferably a homopolymer of chloroprene or a copolymer of at least chloroprene and 2,3-dichloro-1,3-butadiene as monomer components, and more preferably a copolymer of chloroprene and 2,3-dichloro-1,3-butadiene.

[0050] The other copolymerizable monomers that may be contained in the chloroprene copolymer constituting the chloroprene polymer latex (A) of the present embodiment are not particularly limited as long as they are monomers copolymerizable with at least one of the above-mentioned chloroprene and 2,3-dichloro-1,3-butadiene, and specific examples thereof include 1-chloro-1,3-butadiene, butadiene, isoprene, styrene, acrylonitrile, acrylic acid and its esters, methacrylic acid and its esters, and the like.

[0051] Regarding the chloroprene polymer constituting the chloroprene polymer latex (A) of the present embodiment, when the sum of chloroprene, 2,3-dichloro-1,3-butadiene and other copolymerizable monomer components is 100 parts by mass, the units derived from the chloroprene are preferably 80 parts by mass or more, more preferably 85 parts by mass or more, and even more preferably 88 parts by mass or more. The upper limit is preferably 100 parts by mass or less.

[0052] In addition, when a unit derived from 2,3-dichloro-1,3-butadiene is included, it is sufficient as long as it is included in an amount of more than 0 parts by mass, and the upper limit is preferably less than 20 parts by mass, more preferably less than 15 parts by mass, and further preferably less than 12 parts by mass. Other copolymerizable monomers are preferably included in an amount of 5 parts by mass or less.

[0053] The latex composed of a chloroprene polymer having a monomer component composition within the above range is preferred because the crystallization of the chloroprene polymer is suppressed and thus tackiness is imparted, thereby increasing the adhesive strength of the adhesive layer.

[0054] The average particle size of the chloroprene polymer particles constituting the latex is preferably 50 nm or more, more preferably 70 nm or more, and further preferably 90 nm or more. In addition, the upper limit of the average particle size is preferably 500 nm or less, more preferably 300 nm or less, and further preferably 210 nm or less.

[0055] The latex having an average particle size of chloroprene polymer particles in the above range is preferred because the latex particles have low emulsion stability and the emulsion system is rapidly broken during bonding to exhibit adhesive strength, thereby increasing the adhesive strength of the adhesive layer.

[0056] The content of the gel component of the chloroprene polymer in the chloroprene polymer latex (A) is preferably more than 0% by mass, preferably 10% by mass or more, more preferably 20% by mass or more. The upper limit is 50% by mass or less, preferably 45% by mass or less, more preferably 40% by mass or less.

[0057] When the content of the gel component is within the above range, the latex containing the chloroprene polymer has excellent heat creep resistance and high adhesiveness because a cross-linked structure is formed in the chloroprene polymer.

[0058] For the same reason, in the present embodiment, it is desirable that the adhesive composition containing the chloroprene polymer latex does not substantially contain a crosslinking agent. In general, examples of crosslinking agents include polyisocyanate compounds, carbodiimide compounds, When an oxazoline compound or the like contains a cross-linking agent, the storage stability of the composition may be reduced.

[0059] Two or more chloroprene polymer latexes (A) may be used in combination.

[0060] The method for obtaining the chloroprene polymer latex (A) is not limited. In one embodiment, chloroprene alone, or chloroprene and 2,3-dichloro-1,3-butadiene, and other copolymerizable monomers as required, are subjected to emulsion polymerization in the presence of an emulsifier, preferably a metal salt of rosin acid, using a polymerization initiator and a chain transfer agent as required, and when a predetermined polymerization conversion rate is reached, a polymerization inhibitor is added to stop the polymerization.

[0061] The type of emulsifier of the chloroprene polymer latex (A) of the present embodiment is not particularly limited, and examples thereof include anionic emulsifiers and nonionic emulsifiers, and anionic emulsifiers are particularly preferred. These emulsifiers may be used alone or in combination of two or more.

[0062] The type of anionic emulsifier is not particularly limited, and examples thereof include alkali metal salts of rosin acid, dodecylbenzenesulfonates (sodium dodecylbenzenesulfonate, triethanolamine dodecylbenzenesulfonate, etc.), diphenyl ether sulfonates (sodium diphenyl ether sulfonate, ammonium diphenyl ether sulfonate, etc.), naphthalenesulfonates (sodium salt of β-naphthalenesulfonic acid formaldehyde condensate, etc.), and alkali metal salts of fatty acids (potassium laurate, etc.). Alkali metal salts of disproportionated rosin acid are particularly preferred.

[0063] The type of rosin acid is not particularly limited, and examples thereof include gum rosin, wood distilled rosin, tall oil rosin, disproportionated rosin obtained by disproportionation reaction of these, refined rosin, etc., preferably disproportionated rosin. The metal salt generally uses an alkali metal salt, preferably a sodium salt and / or a potassium salt. In addition, rosin acid and an alkali metal hydroxide can be added separately to prepare an alkali metal salt of rosin acid.

[0064] The type of nonionic emulsifier is not particularly limited, and examples thereof include partially saponified polyvinyl alcohol, polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene lauryl ether, and the like. Partially saponified polyvinyl alcohol is particularly preferred.

[0065] These emulsifiers may be used alone or in combination of two or more.

[0066] In this embodiment, it is preferred that a rosin acid metal salt be contained as an emulsifier.

[0067] In the case of containing rosin acid metal salt, its content is preferably 0.5 mass parts or more, more preferably 1.0 mass parts or more, and further preferably 1.5 mass parts or more relative to 100 mass parts of added monomers. The upper limit of the content of rosin acid metal salt is 8 mass parts or less, more preferably 6.5 mass parts or less, and further preferably 5.0 mass parts or less. By making the content of rosin acid metal salt the above range, the polymerization stability in emulsion polymerization can be improved, and the number of micelles formed can be appropriately suppressed to suppress the heat generation in the initial stage of polymerization, and the viscosity in polymerization can be controlled within a specified range. Although the content of rosin acid metal salt is based on the added monomer, it has the same meaning as the solid content benchmark of the polymer, which is equivalent to the content in the chloroprene polymer latex (A).

[0068] The solid content concentration of the chloroprene polymer latex (A) is preferably 35% by mass or more, more preferably 40% by mass or more, and further preferably 45% by mass or more. The upper limit of the solid content concentration of the chloroprene polymer latex (A) is preferably 65% ​​by mass or less, and more preferably 60% by mass or less.

[0069] If the solid content concentration is within the above range, the drying time of the chloroprene polymer latex (A) can be reduced and the load of the drying device can be reduced. In addition, if the solid content concentration is within the above range, it is easier to maintain the colloid stability of the chloroprene polymer latex (A), and the generation of coagulation can be minimized. It should be noted that the dispersion medium is usually water.

[0070] The solid content in the present embodiment is a component obtained by removing components that volatilize under solid content measurement conditions such as solvents and volatile components from the latex or emulsion. The solid content of the chloroprene polymer latex (A) includes, in addition to the chloroprene polymer, an emulsifier used in the production, such as abietic acid metal salts.

[0071] <Thickener (B)>

[0072] The tackifier (B) is added to improve the adhesiveness of the adhesive composition containing the chloroprene polymer latex and the contact property of the chloroprene polymer, and can improve the contact property when a polyolefin is used as an adherend in particular.

[0073] The amount of the tackifier (B) is preferably more than 5 parts by mass, 10 parts by mass or more, and more preferably 18 parts by mass or more, relative to 100 parts by mass of the solid content of the chloroprene polymer latex (A). The upper limit is less than 30 parts by mass, preferably 25 parts by mass or less, and more preferably 22 parts by mass or less. By including the tackifier (B) within the above range, the adhesion of the adhesive composition containing the chloroprene polymer latex and the contact adhesion of the chloroprene polymer can be improved, and the heat creep resistance with the adherend can be improved.

[0074] Regarding the softening point of the tackifier (B), at least one is 85° C. or higher, preferably 90° C. or higher. The upper limit of the softening point of the tackifier (B) is not particularly limited, but is preferably 250° C. or lower, more preferably 200° C. or lower. When the tackifier (B) has a softening point within the above range, the adhesive property of the adhesive composition containing the chloroprene polymer latex can be maintained at high temperatures, and the heat creep resistance can be improved.

[0075] The tackifier (B) may be used alone or in combination of two or more. When two or more tackifiers (B) are used, at least one has a softening point of 85°C or higher. When two or more tackifiers are used, preferably all tackifiers (B) have a softening point of 85°C or higher.

[0076] In addition, when the thickener (B) is used as an emulsion or a solution as mentioned later, the said amount is the solid content amount excluding the solvent etc.

[0077] The type of tackifier (B) is not particularly limited, and examples thereof include rosin resins or rosin ester resins, terpene phenol resins, aliphatic petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, copolymer petroleum resins, petroleum resins such as hydrogenated products thereof, and alkylphenol resins.

[0078] As rosin resin and rosin ester resin, gum rosin, tall oil rosin, wood distilled rosin, disproportionated rosin, polymerized rosin, their hydrogenates, their esters, etc. can be cited, and as terpene phenol resin, hydrogenates of terpene phenol resin, etc. can be cited. The above-mentioned tackifier (B) preferably contains at least one of rosin resin, terpene phenol resin, and alicyclic petroleum resin, and more preferably at least one selected from rosin ester resin and terpene phenol resin. It should be noted that the rosin resin and rosin ester resin used in the tackifier (B) are different from the alkali metal salt of rosin acid and do not constitute an alkali metal salt.

[0079] As a method for adding the tackifier (B), an emulsion of the tackifier (B) is generally mixed with the above-mentioned chloroprene polymer latex (A), but the tackifier (B) itself can also be added during the production process of the chloroprene polymer latex (A). This method of adding is effective as one of the methods for adding a tackifier (B) of a type whose emulsion is not commercially available.

[0080] Commercially available products of the tackifier (B) that can be used in the present embodiment include Super Ester (registered trademark) E-900-NT manufactured by Arakawa Chemical Industries, Ltd., which is a polymerized rosin-based emulsion, E-720W manufactured by Taiwan Arakawa Chemical Industries, Ltd., which is a rosin-based emulsion, Hari Ester SK-218NS, Hari Ester SK-323NS, and Hari Ester SK-508H manufactured by Harima Chemicals, Tamanol (registered trademark) E-100, Tamanol (registered trademark) E-200NT, and Tamanol (registered trademark) E-102A manufactured by Arakawa Chemical Industries, Ltd., which are terpene phenol resin emulsions, and TR-602 manufactured by BASF. In addition, as the solid thickener (B), there is Alcon (registered trademark) M-135 manufactured by Arakawa Chemical Industries, Ltd., which is an alicyclic petroleum resin.

[0081] <Chlorinated polyolefin resin (C)>

[0082] The chlorinated polyolefin resin (C) is a resin obtained by chlorinating a polyolefin. The chlorinated polyolefin resin (C) is a component that contributes to imparting adhesion to a non-polar material such as a polyolefin resin to an adhesive composition containing a chloroprene polymer latex.

[0083] The content of the chlorinated polyolefin resin (C) is 6 parts by mass or more, preferably 8 parts by mass or more, and more preferably 10 parts by mass or more, based on 100 parts by mass of the solid content of the chloroprene polymer latex (A). The upper limit of the content is less than 30 parts by mass, preferably 25 parts by mass or less, and more preferably 22 parts by mass or less.

[0084] By adding the chlorinated polyolefin resin (C), good adhesion to the polyolefin resin can be made high, and if it is in the above numerical range, the heat creep resistance can be maintained high, and the cost performance is excellent. It should be noted that, when the chlorinated polyolefin resin (C) is used in the form of an emulsion or a solution as described later, the above amount is the solid content amount excluding the components such as the solvent and volatile components that volatilize under the solid content measurement conditions, and when a surfactant is included, the amount including the surfactant is also the solid content.

[0085] The softening point of the chlorinated polyolefin resin (C) is less than 80° C., preferably 75° C. or less, and more preferably 70° C. or less. The lower limit of the softening point of the chlorinated polyolefin resin (C) is preferably 40° C. or more. By including the chlorinated polyolefin resin (C) having a softening point in the above range, the chlorinated polyolefin resin (C) is compatible with the chloroprene polymer during drying, and the adhesiveness with the polypropylene resin is improved.

[0086] As the raw material of the chlorinated polyolefin resin (C), any known raw material for the chlorinated polyolefin resin may be freely selected and used as long as the effects of the present embodiment are not impaired, and examples thereof include crystalline polypropylene, non-crystalline polypropylene, polybutene-1, low-density or high-density polyethylene, ethylene / propylene copolymer, ethylene / propylene / diene copolymer, and the like.

[0087] The chlorinated polyolefin resin (C) is preferably an acid-modified chlorinated polyolefin resin graft-polymerized with at least one monomer selected from α,β-unsaturated carboxylic acids and their anhydrides. Examples of the α,β-unsaturated carboxylic acids and their anhydrides used herein include maleic acid, itaconic acid, citraconic acid, fumaric acid, mesaconic acid, aconitic acid, maleic anhydride, itaconic anhydride, citraconic anhydride, aconitic anhydride, and the like. If the chlorinated polyolefin resin (C) is acid-modified, when a metal oxide such as zinc oxide or magnesium oxide is mixed in the adhesive, crosslinking of polyvalent metal ions and carboxyl groups occurs, and thus adhesive properties such as heat creep resistance and solvent resistance can be improved.

[0088] The chlorine content of the chlorinated polyolefin resin (C) is not particularly limited, but is preferably 10% by mass or more, preferably 16% by mass or more, and more preferably 18% by mass or more. The upper limit is preferably 40% by mass or less, more preferably 22% by mass or less, and further preferably 21% by mass or less. When the chlorine content of the chlorinated polyolefin resin (C) is within the above range, the adhesive force to non-polar materials, particularly polyolefin resins, etc. is improved.

[0089] In another aspect of the present embodiment, the adhesive composition containing chloroprene polymer latex contains chloroprene polymer latex (A), tackifier (B) and chlorinated polyolefin resin (C), wherein the softening point of the tackifier (B) is higher than the softening point of the chlorinated polyolefin resin (C) by 5°C or more. In this aspect, the content of the gel component of the chloroprene polymer latex (A) is not particularly limited, and the softening point of the tackifier (B) itself is not particularly limited as long as the softening point difference between the tackifier (B) and the chlorinated polyolefin resin (C) is 5°C or more, but is preferably the above-exemplified one.

[0090] As long as the chlorinated polyolefin resin (C) can be mixed with the chloroprene polymer latex (A) and the tackifier (B), there is no particular limitation on the form in which it is used, but usually, an emulsion dispersed in a dispersion medium is used. In addition, for emulsification, a surfactant may be appropriately included in the emulsion. The surfactant used in the emulsion of the chlorinated polyolefin resin (C) is also not particularly limited as long as it does not impair the effect of the present embodiment, and examples thereof include nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants. In the present technology, it is preferred to use a nonionic surfactant from the viewpoint of the storage stability of the adhesive composition.

[0091] Commercially available products that can be used as the chlorinated polyolefin resin (C) include water-based chlorinated polyolefin Superchloron (registered trademark) E-480T manufactured by Nippon Paper Industries, Ltd., and the like.

[0092] The solid content concentration of the chlorinated polyolefin resin (C) emulsion is preferably 15% by mass or more, more preferably 20% by mass or more. In addition, the upper limit is 60% by mass or less, more preferably 45% by mass or less. If the solid content concentration is within the above range, the viscosity is appropriate and it is easy to mix with the chloroprene polymer latex (A) and the tackifier (B). It should be noted that the dispersion medium is usually water. As an additive, a water-compatible solvent such as ethylene glycol and ethanol may be included.

[0093] The chlorinated polyolefin resin (C) may be used in combination of two or more kinds.

[0094] <Metal oxides or hydroxides>

[0095] The adhesive composition containing the chloroprene polymer latex according to the present embodiment may contain a metal oxide or hydroxide in addition to the chloroprene polymer latex (A), the tackifier (B), and the chlorinated polyolefin resin (C).

[0096] The metal oxide or hydroxide is preferably a polyvalent metal oxide or hydroxide, and more preferably a divalent metal oxide or hydroxide of a metal other than an alkaline earth metal.

[0097] The metal oxide or hydroxide is added to improve the adhesion and heat creep resistance of the adhesive composition. In particular, if a carboxyl group is included in the adhesive composition, crosslinking of the polyvalent metal ion and the carboxyl group occurs, thereby further improving the heat creep resistance. In addition, the adhesion when a polyolefin is used as an adherend can be improved.

[0098] Metal oxide or hydroxide is preferably used relative to the solid component conversion of chloroprene polymer latex (A) as 100 mass parts and as 0.3 mass parts or more, more preferably as 0.5 mass parts or more, more preferably as 1.0 mass parts or more. In addition, the upper limit is below 10 mass parts, more preferably below 7 mass parts, more preferably below 5 mass parts. Heat creep resistance can be improved by adding metal oxide or hydroxide. In addition, by adding in the above range, the reduction of initial bonding strength and contact adhesion can be prevented, and the cost is reduced.

[0099] The metal oxide or hydroxide used in the present embodiment is not particularly limited, and specifically zinc oxide, magnesium oxide, zinc hydroxide, magnesium hydroxide, etc. can be cited, and zinc oxide and magnesium oxide are more preferably used. These metal oxides can also be used in combination with two or more. Among them, zinc oxide and chloroprene polymer are easy to ion crosslink, which is preferred.

[0100] In addition, in order to quickly mix with the water-based adhesive, it is preferably added in a form dispersed in water. Commercially available products that can be used in the present embodiment include AZ-SW manufactured by Osaki Industries, Ltd., and the like.

[0101] The adhesive composition containing chloroprene polymer latex according to the present embodiment is produced by mixing metal oxides, hydroxides and the like with chloroprene polymer latex (A), tackifier (B) and chlorinated polyolefin resin (C) as needed.

[0102] The mixing method is not particularly limited, and a known method such as a mixer can be used.

[0103] To the adhesive composition containing the chloroprene polymer latex of the present embodiment, a filler, a pigment, a colorant, a wetting agent, a defoaming agent, a thickener, and the like may be optionally added.

[0104] The composition of the present embodiment is also preferably in a form containing a thickener. As the thickener, the SN Squinner series (manufactured by Sannopoco Co., Ltd.) containing urethane-modified polyether can be used.

[0105] The solid content concentration and viscosity of the obtained adhesive composition containing the chloroprene polymer latex are appropriately adjusted according to the purpose. For example, a known method such as evaporation or addition of water is used as the adjustment method.

[0106] In this embodiment, the adhesive layer is formed from the above-mentioned adhesive composition containing chloroprene polymer latex.

[0107] The manufacturing method of the adhesive layer is not limited, and the adhesive layer can be manufactured by applying the adhesive composition to the adherend surface on the substrate side, drying at a temperature of 40°C or higher for more than 3 minutes, and heating the other adherend at a temperature of 130°C or higher for more than 1 minute to bond. The so-called substrate is a material with sufficient strength and rigidity among the adherends, and examples thereof include resins and metals. As resins, there are polyethylene, polypropylene, and ABS resins, and as metals, there are iron and aluminum.

[0108] The drying temperature is preferably 60°C or higher, more preferably 80°C or higher.

[0109] As the adherend, there is no particular limitation as long as it is a material that can be coated, and it can be used for bonding foams, sheets, films, canvas, glass, etc. In particular, since the adhesiveness to difficult-to-bond polyolefins and polyurethanes is high, it is effective when at least one of the adherends is these.

[0110] Among them, the composition of this embodiment exhibits a high effect when at least one of the adherends is a laminate of a foamed organic material, and exhibits a higher effect when the foamed organic material is any of poorly adhesive polypropylene, polyethylene, and polyurethane.

[0111] The coating method is not particularly limited, and known methods such as brushing, knife coating, spraying, dipping, and coater can be used. The thickness of the adhesive layer is not particularly limited as long as the adhesive strength can be maintained, and is usually about 20 to 100 μm after drying, but is not particularly limited.

[0112] Furthermore, in the present embodiment, it is a laminated body in which adherends are laminated via the above-mentioned adhesive layer.

[0113] That is, the laminated body involved in this embodiment is formed by laminating two adherends via the above-mentioned adhesive composition containing chloroprene polymer latex, and at least one of the above-mentioned adherends is polyolefin. Even if the two adherends are of the same material, they can be used without special restrictions. In addition, the manufacturing method of such a laminated body is also not particularly limited. After an adhesive layer is pre-arranged in one or both of the adherends, the adherends are laminated and bonded. In order to firmly bond, the laminated body can be pressurized, and the pressurization can be performed on the whole or only on the part where the adhesive layer is provided. There is no special restriction on the pressurization method. In addition, the pressure is also not particularly limited as long as it is a pressure to the extent that the adhesive layer is not significantly deformed.

[0114] Example

[0115] The present invention will be described below with reference to Examples and Comparative Examples, but the present invention is not limited to the following examples.

[0116] The physical properties shown in Examples and Comparative Examples were measured under the following conditions and measurement methods.

[0117] [Measurement method]

[0118] 1) Solid content concentration

[0119] The solid content concentration of the emulsion of the chloroprene polymer latex (A), the tackifier (B) and the chlorinated polyolefin resin (C) was calculated from the mass before drying and the mass after drying by heat-treating 1 g of the emulsion of the chloroprene polymer latex (A), the tackifier (B) or the chlorinated polyolefin resin (C) in an aluminum dish having a diameter of 39 mm in the air (at 141° C. for 30 minutes) to dry it to only the solid content.

[0120] Solid content concentration (mass %) = [(mass of latex or emulsion after drying at 141°C for 30 minutes) / (mass of latex or emulsion before drying)] × 100

[0121] 2) Polymerization conversion rate of chloroprene polymer

[0122] About 1 g of the chloroprene polymer latex (A) was accurately weighed into an aluminum dish, dried in an oven at 141°C for 30 minutes, and then cooled in a desiccator to room temperature. The mass was measured and taken as the mass of the non-volatile component. The polymerization conversion rate was calculated by setting the theoretical non-volatile component ratio of the reaction solution when all monomers such as chloroprene and 2,3-dichloro-1,3-butadiene were polymerized to form non-volatile components as 100%.

[0123] The polymerization conversion rate was calculated according to the formula (1).

[0124] Polymerization conversion rate [%] = [(polymer production amount / monomer addition amount)] × 100 (1)

[0125] When calculating the polymer yield of the chloroprene polymer latex (A), the yield is calculated by subtracting the contents of tackifiers, surfactants (except those used in the polymerization of the chloroprene polymer latex (A)), vulcanization accelerators, metal oxides such as zinc oxide dispersions, acid acceptors, antioxidants, fillers, pigments, colorants, wetting agents, defoaming agents, thickeners, etc. from the mass of non-volatile components.

[0126] 3) Gel content

[0127] 1 g of chloroprene polymer latex (A) (water content: 35-65% by mass) was added dropwise to 100 ml of tetrahydrofuran (hereinafter also referred to as "THF") and shaken for 12 hours. The dissolved phase of the supernatant was separated by a centrifugal separator, and THF was evaporated / dry-cured at 100°C for 1 hour, and the mass of the dried solid was measured. Since the mass of the dried solid is the mass of the tetrahydrofuran-soluble component in the chloroprene polymer, the mass of the tetrahydrofuran-soluble component was subtracted from the mass of the chloroprene polymer, and the value was set as the mass of the gel, and the content of the gel component in the chloroprene polymer was calculated. It should be noted that the mass of the chloroprene polymer is almost the same as the mass of the solid content of the chloroprene polymer latex (A), so this value can be used.

[0128] Gel content (%) = ((mass of chloroprene polymer (g)) - (mass of dried solidified product (g))) ÷ (mass of chloroprene polymer) × 100

[0129] 4) Average particle size

[0130] The average particle size was measured by diluting the latex or emulsion to 0.01 to 0.1% by mass with pure water, and using a dynamic light scattering photometer (ZETASIZER (registered trademark) Nano-S manufactured by Malvern Panalytical Ltd.) to obtain a solution having a z average particle size.

[0131] 5) Softening point

[0132] 1 g of the tackifier (B) or the chlorinated polyolefin resin (C) was added to 100 mL of tetrahydrofuran, and the mixture was shaken for 10 hours using a shaker (SA300) manufactured by Yamato Scientific Co., Ltd. to dissolve the mixture.

[0133] The solution after shaking was added dropwise to 500 mL of methanol, and the generated solidified product was filtered out with a stainless steel sieve of 80 meshes and dried overnight in a desiccator.

[0134] The obtained dried solidified product was measured by the ring and ball method according to JIS K2207-1996. The sample was melted at low temperature so as not to generate bubbles, and the melted sample was filled in a ring preheated to an appropriate temperature, and the softening point was measured using a glycerin bath with an automatic softening point evaluation device.

[0135] 6) Chlorine content

[0136] The chlorine content in the chlorinated polyolefin (C) was quantitatively determined by an oxygen bottle combustion method or a silver nitrate titration method in accordance with JIS K7229-1995.

[0137] The chlorine content was determined by dividing the above chlorine content by the mass of the chlorinated polyolefin (C), and multiplying the result by 100.

[0138] 7) Adhesion

[0139] The test piece for the adhesion test described below was subjected to a 180° peel test according to the method of JIS K6854-2-1999. Regarding the adhesion, the normal adhesion (kN / m) was measured. It should be noted that the adhesion is the value measured by performing a peel test after curing at 23°C and 60% RH (relative humidity) for 1 day after pasting.

[0140] 8) Thermal creep resistance

[0141] After the test piece for the adhesive strength test described below was cured at 23°C for 1 day, a load of 100 g / 25 mm was applied in a 90° direction at 90°C, and the peeling length after 24 hours was measured as heat-resistant creep.

[0142] 9) Storage stability of adhesive composition

[0143] The adhesive composition described below was added to a 150 mL disposable cup made of polypropylene, the cup mouth was sealed with a sealing film (Parafilm), and it was left at room temperature for 3 days. The cup was tilted, and the storage stability was good when the adhesive composition flowed, and the storage stability was NG when it did not flow, that is, it was solidified.

[0144] [Preparation of Adhesive Composition Containing Chloroprene Polymer Latex]

[0145] To the chloroprene polymer latex (A) obtained in each preparation example, a tackifier (B), a chlorinated polyolefin resin (C), and other additives were added (mixed) in the amounts shown in Tables 1 and 2 to prepare an adhesive composition containing a chloroprene polymer latex.

[0146] [Preparation of each test piece]

[0147] 1) Test piece for adhesion test

[0148] 150g (solid content) / m 2Each adhesive composition containing chloroprene polymer latex was applied to a polypropylene natural color plate (100 mm wide × 200 mm long × 3 mm thick, coated surface 100 mm wide × 100 mm long) using a sprayer with a diameter of 1.5 mm, dried at 80°C for 5 minutes, and then cooled at room temperature for 2.5 minutes. A polypropylene foam (100 mm wide × 200 mm long × 15 mm thick, coated surface 100 mm wide × 100 mm long) was dried at 150°C for 2 minutes and bonded to the polypropylene natural color plate, and then pressed with a 5 kg hand roller reciprocating 4 times and cut into 25 mm wide pieces, which were used as test pieces for adhesion test.

[0149] Formulation Example 1

[0150] [Production of Chloroprene Polymer Latex (A)-1]

[0151] Into a reactor having an internal volume of 5 L were added 1830 g of chloroprene monomer, 170 g of 2,3-dichloro-1,3-butadiene, 86 g of disproportionated rosin (R-600 manufactured by Arakawa Chemical Industries, Ltd.), 1715 g of pure water, 22.8 g of potassium hydroxide, 5.2 g of sodium hydroxide, 1.2 g of n-dodecyl mercaptan (molecular weight modifier), and 10.4 g of condensed sodium naphthalenesulfonate solution (trade name SN-PW-43 (manufactured by Sannopoco Co., Ltd.)) and emulsified.

[0152] To the emulsion, 5.6 g of potassium sulfite was added, followed by 1.2 g of potassium persulfate as a polymerization initiator, and polymerization was carried out at 40° C. in a nitrogen atmosphere. After the polymerization conversion rate reached 88%, 0.4 g of phenothiazine was immediately added to stop the polymerization. Then, unreacted chloroprene was removed by steam stripping to obtain chloroprene polymer latex (A)-1. The content of the gel component of the chloroprene polymer in the chloroprene polymer latex (A)-1 was 42% by mass, the solid content concentration of the chloroprene polymer latex (A)-1 was 50% by mass, and the average particle size was 130 nm.

[0153] Formulation Example 2

[0154] [Production of Chloroprene Polymer Latex (A)-2]

[0155] Into a reactor having an internal volume of 5 L were added 2000 g of chloroprene monomer, 34.2 g of disproportionated rosin (R-600 manufactured by Arakawa Chemical Industries, Ltd.), 1211 g of pure water, 21.3 g of potassium hydroxide, 3.6 g of n-dodecyl mercaptan (molecular weight modifier), and 24 g of condensed sodium naphthalenesulfonate solution (trade name SN-PW-43 (manufactured by Sannopoco Co., Ltd.)) and emulsified.

[0156] To the emulsion, 2.0 g of potassium sulfite was added, followed by 1.0 g of potassium persulfate as a polymerization initiator, and polymerization was carried out at 45° C. in a nitrogen atmosphere. After the polymerization conversion rate reached 90%, 0.4 g of phenothiazine was immediately added to stop the polymerization. Then, unreacted chloroprene was removed by steam stripping to obtain chloroprene polymer latex (A)-2. The content of the gel component of the chloroprene polymer in the chloroprene polymer latex (A)-2 was 13% by mass, the solid content concentration of the chloroprene polymer latex (A)-2 was 58% by mass, and the average particle size was 200 nm.

[0157] Formulation Example 3

[0158] [Production of Chloroprene Polymer Latex (A)-3]

[0159] Into a reactor having an internal volume of 5 L were added 1600 g of chloroprene, 56 g of disproportionated rosin (R-600 manufactured by Arakawa Chemical Industries, Ltd.), 1444 g of pure water, 14.4 g of sodium hydroxide, 1.8 g of n-dodecyl mercaptan (molecular weight modifier), and 22.6 g of condensed sodium naphthalenesulfonate solution (trade name SN-PW-43 (manufactured by Sannopoco Co., Ltd.)) and emulsified.

[0160] To the emulsion, 4.8 g of potassium sulfite was added, followed by the addition of 0.8 g of potassium persulfate as a polymerization initiator, and polymerization was carried out at 15° C. in a nitrogen atmosphere. After the polymerization conversion rate reached 78%, 0.5 g of phenothiazine was immediately added to stop the polymerization. Then, the unreacted chloroprene was removed by steam stripping to obtain chloroprene polymer latex (A)-3. The content of the gel component of the chloroprene polymer in the chloroprene polymer latex (A)-3 was 0% by mass, the solid content concentration of the chloroprene polymer latex (A)-3 was 58% by mass, and the average particle size was 130 nm.

[0161] Formulation Example 4

[0162] [Production of Chloroprene Polymer Latex (A)-4]

[0163] Into a reactor having an internal volume of 5 L were added 1830 g of chloroprene, 170 g of 2,3-dichloro-1,3-butadiene, 86 g of disproportionated rosin (R-600 manufactured by Arakawa Chemical Industries, Ltd.), 1715 g of pure water, 22.8 g of potassium hydroxide, 5.2 g of sodium hydroxide, and 10.4 g of condensed sodium naphthalenesulfonate solution (trade name SN-PW-43 (manufactured by Sannopoco Co., Ltd.)) and emulsified.

[0164] To the emulsion, 5.6 g of potassium sulfite was added, followed by 1.2 g of potassium persulfate as a polymerization initiator, and polymerization was carried out at 40° C. under a nitrogen atmosphere. After the polymerization conversion rate reached 88%, 0.4 g of phenothiazine was immediately added to stop the polymerization. Then, the unreacted chloroprene was removed by steam stripping to obtain chloroprene polymer latex (A)-4. The gel content of the chloroprene polymer in the chloroprene polymer latex (A)-4 was 79% by mass, the solid content concentration of the chloroprene polymer latex (A)-4 was 50% by mass, and the average particle size was 130 nm.

[0165] Formulation Example 5

[0166] [Production of Chloroprene Polymer Latex (A)-5]

[0167] Into a reactor having an internal volume of 5 L were added 2000 g of chloroprene monomer, 34.2 g of disproportionated rosin (R-600 manufactured by Arakawa Chemical Industries, Ltd.), 1211 g of pure water, 21.3 g of potassium hydroxide, 1.0 g of n-dodecyl mercaptan (molecular weight modifier), and 24 g of condensed sodium naphthalenesulfonate solution (trade name SN-PW-43 (manufactured by Sannopoco Co., Ltd.)) and emulsified.

[0168] To the emulsion, 2.0 g of potassium sulfite was added, followed by 1.0 g of potassium persulfate as a polymerization initiator, and polymerization was carried out at 45° C. under a nitrogen atmosphere. After the polymerization conversion rate reached 90%, 0.4 g of phenothiazine was immediately added to stop the polymerization. Then, the unreacted chloroprene was removed by steam stripping to obtain chloroprene polymer latex (A)-5. The content of the gel component of the chloroprene polymer in the chloroprene polymer latex (A)-5 was 87% by mass, the solid content concentration of the chloroprene polymer latex (A)-5 was 58% by mass, and the average particle size was 200 nm.

[0169] Example 1

[0170] 100 parts by mass of chloroprene polymer latex (A)-1 as chloroprene polymer latex (A) in terms of solid content, 20 parts by mass of Super Ester E-720W (produced by Arakawa Chemical Industries) as a tackifier (B) in terms of solid content (solid content concentration: 50% by mass), and 20 parts by mass of Super Crosin as an emulsion of a chlorinated polyolefin resin (C) in terms of solid content (solid content concentration: 30% by mass) were added. An adhesive composition containing a chloroprene polymer latex was obtained by uniformly stirring a 10% by mass dilution of AZ-SW (manufactured by Osaki Kogyo Co., Ltd.) (solid content concentration: 50% by mass) as zinc oxide in terms of solid content, and 0.3 parts by mass of SN Silicone 612 (manufactured by Sannopco Co., Ltd.) (solid content concentration: 40% by mass) as a thickener.

[0171] Examples 2 to 7, Comparative Examples 1 to 14

[0172] In Example 1, the type and amount of the chloroprene polymer latex (A), the type and amount of the tackifier (B), the amount of the emulsion of the chlorinated polyolefin resin (C), and the newly added crosslinking agent were changed to prepare an adhesive composition, thereby obtaining the adhesive compositions described in Tables 1 and 2. The results of the adhesive strength evaluation and the heat creep test are also described in Tables 1 and 2.

[0173] Table 1 shows the examples, and Table 2 shows the comparative examples.

[0174] [Table 1]

[0175]

[0176] [Table 2]

[0177]

[0178] The reagents are listed in Tables 3 to 5.

[0179] [Table 3]

[0180] Chloroprene polymer latex (A) Content of gel component (A)-1 37% by mass (A)-2 22% by mass (A)-3 0% by mass (A)-4 79% by mass (A)-5 87% by mass

[0181] [Table 4]

[0182] Tackifier (B) Manufacturer name Resin type Rosin type Softening point Super Ester E-720W Arakawa Chemical Industries Rosin Rosin ester 100℃ SNOWTACK 100G LAWTER Rosin Rosin ester 100℃ DERMULSENE RE 1513 DRT Rosin Rosin ester 82℃ AQUATAC 6025 KRATON Rosin Rosin ester 25℃ Super Ester E-900-NT Arakawa Chemical Industries Rosin Polymerized rosin 160℃ Tamanol E-100 Arakawa Chemical Industries Terpene phenol - 150℃

[0183] [Table 5]

[0184]

[0185] [Table 6]

[0186] Crosslinking agent Manufacturer name Compound name WB40-100 Asahi Kasei 1,6-Hexamethylene diisocyanate

[0187] As is clear from Examples 1 to 7 in Table 1, a chloroprene polymer latex (A), a tackifier (B) and a chlorinated polyolefin resin (C) are contained, the content of the gel component of the chloroprene polymer in the chloroprene polymer latex (A) exceeds 0% by mass and is less than 50% by mass, at least one of the tackifiers (B) has a softening point of 85° C. or higher, the chlorinated polyolefin resin (C) has a softening point of less than 80° C., and relative to 100 parts by mass of the solid content of the chloroprene polymer latex (A), The amount of the tackifier (B) is more than 5 parts by mass and less than 30 parts by mass, the amount of the chlorinated polyolefin resin (C) is more than 6 parts by mass and less than 30 parts by mass relative to 100 parts by mass of the solid content of the chloroprene polymer latex (A), and the adhesive composition containing the chloroprene polymer latex without a crosslinking agent has a high adhesion strength of 0.61 to 1.14 kN / m to a polypropylene plate and a polypropylene foam, and a peeling length in a heat-resistant creep test is less than 10 mm, showing good heat resistance.

[0188] Furthermore, it is clear from Examples 1 to 7 that regardless of the added amounts of zinc oxide and thickener, good adhesion to polypropylene and heat resistance are exhibited.

[0189] On the other hand, in Comparative Examples 1 to 3 in Table 2, where the content of the gel component of the chloroprene polymer in the chloroprene polymer latex (A) was 0% by mass or exceeded 50% by mass, the heat creep resistance was insufficient.

[0190] Furthermore, in Comparative Examples 4 and 5 containing 5 parts by mass or less or 30 parts by mass or more of the tackifier (B) relative to 100 parts by mass of the solid content of the chloroprene polymer latex (A), the heat creep resistance was insufficient. In addition, in Comparative Examples 6 and 7 in which the softening point of the tackifier (B) was less than 85° C., the heat creep resistance was insufficient.

[0191] Furthermore, in Comparative Examples 8 to 10 containing less than 6 parts by mass or more than 30 parts by mass of the chlorinated polyolefin resin (C) relative to 100 parts by mass of the solid content of the chloroprene polymer latex (A), the heat creep resistance was insufficient. In addition, in Comparative Examples 11 to 13 in which the softening point of the chlorinated polyolefin resin (C) was 80° C. or more, the heat creep resistance was insufficient.

[0192] Furthermore, in Comparative Example 14 containing 2 parts by mass of the crosslinking agent WB40-100 based on 100 parts by mass of the solid content of the chloroprene polymer latex (A), the storage stability of the adhesive composition was low.

Claims

1. An adhesive composition containing chloroprene polymer latex, characterized in that: A method of preparing a chlorinated polyolefin resin comprising: comprising a chloroprene polymer latex (A), a tackifier (B) and a chlorinated polyolefin resin (C), wherein the content of the gel component of the chloroprene polymer in the chloroprene polymer latex (A) is more than 0% by mass and less than 50% by mass, at least one of the tackifiers (B) has a softening point of 85° C. or more, and the chlorinated polyolefin resin (C) has a softening point of less than 80° C. The amount of the tackifier (B) is more than 5 parts by mass and less than 30 parts by mass relative to 100 parts by mass of the solid content of the chloroprene polymer latex (A), The chlorinated polyolefin resin (C) is 6 parts by mass or more and less than 30 parts by mass based on 100 parts by mass of the solid content of the chloroprene polymer latex (A), The adhesive composition containing the chloroprene polymer latex does not contain a crosslinking agent. 2 . The adhesive composition containing chloroprene polymer latex according to claim 1 , wherein the chloroprene polymer is a chloroprene homopolymer or a copolymer containing at least chloroprene and 2,3-dichloro-1,3-butadiene.

3. The adhesive composition containing chloroprene polymer latex according to claim 1, wherein the tackifier (B) comprises at least one of rosin resin, rosin ester resin, terpene phenol resin, and alicyclic petroleum resin. 4 . The adhesive composition containing chloroprene polymer latex according to claim 1 , wherein the tackifier (B) has a softening point of 85° C. or higher and 250° C. or lower. 5 . The adhesive composition containing chloroprene polymer latex according to claim 1 , further comprising a metal oxide or hydroxide. 6 . The adhesive composition containing chloroprene polymer latex according to claim 1 , further comprising a thickener. 7 . An adhesive layer comprising the adhesive composition containing a chloroprene polymer latex according to claim 1 . 8 . A laminated body comprising two adherends laminated together via the adhesive composition containing a chloroprene polymer latex according to claim 1 . 9 . The laminate according to claim 8 , wherein at least one of the adherends is a foamed organic material. 10 . The laminate according to claim 9 , wherein the foamed organic material of the laminate is any one of polypropylene, polyethylene, and polyurethane.